The Relationship between Association and Moral Development of Student Learning Activities - Nur Sakinah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
One indicator of decreased student learning activities is student association. In addition, there is a tendency for students' moral development to be unfavorable. Both of these indicators have a significant relationship to the tendency of student learning activities. Therefore, improvements and improvements to social interaction and moral development will have a positive impact on increasing student learning activities. This study aims to see and examine the extent to which the relationship between association and moral development of student learning activities in Madrasah Aliyah Muhammadiyah Mandala Medan.